Strategi Komunikasi Antar Penjual dan Pembeli di Media Sosial dalam Strategi Pemasaran - Agil Hari; Aldo Savero Zahran; Firdi Ahmad Fariji; Muhamad Fauzan Kurniawan; April laksana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research discusses the communication strategy between sellers and buyers on social media as part of an effective marketing strategy. Social media has become a key platform in modern marketing due to its ability to create direct interaction and build relationships between sellers and buyers. The communication strategies applied include the use of relevant content, personal approach, quick response, and utilization of interactive features of social media. The results show that effective communication can increase customer engagement, build trust, expand market reach, and drive increased sales. However, there are challenges in maintaining communication consistency and facing increasing competition in the digital world. Therefore, an innovative and customer-focused approach is required to achieve success in marketing through social media. Communication strategies between sellers and buyers on social media play an important role in supporting the success of marketing strategies in the digital age. Social media has evolved into a major platform for direct interaction between sellers and buyers, offering ease of access, wide reach, and cost-effectiveness compared to traditional marketing methods. This research explores the various communication strategies used by sellers to build relationships with buyers, including the use of relevant and engaging content, a data-driven personalized approach, and prompt responses to customer needs and questions. This research concludes that an effective communication strategy on social media serves not only as a promotional tool, but also as a means to build long-term relationships between sellers and buyers. With the right approach, social media can be a powerful platform to support marketing success, increase customer satisfaction, and achieve overall business goals.